Viabilidade técnica do uso e econômica da produção do agregado de RCD em pavimentação de vias urbanas - Almeida, Jupira (2015)
Civil construction, through new constructions, demolitions and renovations, is responsible for the production of waste, known as RCD Construction and Demolition Waste. These residues are often referred to as environmental liabilities, associated with economic and social issues, due to their inadequate disposition in nature, which, when properly disposed of in landfills, generate another problem, that of unavailability because of their demand, reduce the useful life of these landfills. As one of the alternatives for reuse, the RCD has been evaluated for use in paving layers, aiming at reducing the high costs with the use of materials usual in the construction of bases and sub-bases of these pavements. In order to meet the proposed objectives, the present study evaluated the technical and economic feasibility of the use of the recycled aggregate in the construction of layers of sub-bases for paving of urban roads in the municipality of Passo Fundo. The residues were selected and classified in Class A, transforming them into aggregate, which was evaluated for their technical capacity, being considered suitable for use as a base and / or sub-base for paving of urban roads. The analysis of the technical feasibility later allowed the design of the sub-base layers for the urban paving routes, for which data from the urban roads of the Passo Fundo municipality were used as a model study for light and medium traffic, together with the collection of the quantity of material necessary for the execution of these routes and the quantity of possible waste to process. For the economic viability analysis, a RCD recycling plant plant study was carried out, with an effective capacity of 112 t / day, taking into account the costs for the implementation, operation and maintenance, on which cash flow was generated for the most probable condition, which was not economically viable. Two other scenarios were evaluated, with changes in some parameters, changes in the sale price of the product and increase in the quantity of raw material processed, and these presented economic viability in the cash flows of the entrepreneur in the situation of increase of the processed material and increase in the price of the final product, but did not present viability in the investor's cash flows.